PENGARUH CITRA MEREK DAN LAYANAN PURNA JUAL TERHADAP KEPUASAN KONSUMEN SEPEDA MOTOR HONDA PADA PT. CAPELLA DINAMIK NUSANTARA DURI - Santrisya Munte; Endang Sutrisna (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
This research was conducted at PT. Capella Dinamik Nusantara Duri, the purpose of this study was to determine of brand image and after sales service to consumer satisfaction of Honda motorcycles at PT. Capella Dinamik Nusantara Duri. Brand Image and After Sales Service as an independent variable ) while customer satisfaction as dependent variable (Y)The problem in this research is the number of motorcycle sales that experience Fluctuation in PT. Capella Dinamik Nusantara Duri, in the last 5 years did not reach the target. The sample were taken by 100 respodents from quetionnarire and subsequently processed to then tested with statistics through SPSSFrom the results of tests conducted indicate show that the brand image and after-sales service have a positive and significant impact on customer satisfaction at PT. Capella Dinamik Nusantara Duri.Key words : Brand Image, After Sales Service and Consumer Satisfaction